Gastrointestinal lipoma presenting as colonic intussuception: report of two cases. - Medhi, Pranita; Sharma, Mahak; Biswas, Manjusha (Annals of Pathology and Laboratory Medicine, 2015)
LipomasÂ areÂ benignÂ mesenchymalÂ tumors of adipose tissue,Â thoughÂ commonÂ atÂ otherÂ sites,Â areÂ rareÂ inÂ GIT. MostÂ gastrointestinalÂ lipomasÂ areÂ located Â inÂ theÂ colon,Â ileumÂ and jejunum,Â areÂ rarelyÂ responsibleÂ forÂ clinicalÂ symptoms Â andÂ areÂ usuallyÂ detectedÂ incidentally atÂ colonoscopy. We present two such cases of large colonic lipomas. One is a 38-years old female presentingÂ withÂ complaintÂ ofÂ looseÂ stoolÂ andÂ sessileÂ massÂ inÂ transverseÂ colon onÂ colonoscopy,Â suspectedÂ toÂ beÂ aÂ malignantÂ lesion. TheÂ otherÂ isÂ aÂ 40 yearsÂ oldÂ female presentingÂ withÂ acuteÂ abdomen,Â colonoscopyÂ revealedÂ aÂ submucosalÂ massÂ inÂ descending colon. BothÂ underwentÂ resectionÂ ofÂ mass,Â andÂ histologicallyÂ wereÂ revealedÂ toÂ be lipomas ofÂ colon. ColonicÂ lipomas,Â althoughÂ unusual,Â continueÂ toÂ presentÂ difficultiesÂ inÂ the preoperativeÂ differentiationÂ betweenÂ malignantÂ andÂ benignÂ colonicÂ neoplasm. Two cases of colonicÂ lipomasÂ areÂ reported.